Pengembangan Pendidikan Berbasis Kompetensi perspektif Al-Farabi dan Relevansinya bagi Pengembangan Pendidikan Agama Islam di Era Society 5.0 - Azis, Annisa Rahmania; Salik, Mohammad; Fahmi, Muhammad; Nata, Balqisa Ratu; Zamhariroh, Nazila Mumtaza (UMSU, 2024)
This study aims to analyze the relevance of Al-Farabi's thoughts in the development of competency-based Islamic Religious Education (PAI) in the Society 5.0 era. The research employs a qualitative approach with a literature review method, including an analysis of articles and books related to Al-Farabi's works and ideas, competency-based education, and the challenges faced by PAI in the digital era. The data analysis technique involves an in-depth examination of Al-Farabi's educational principles and their applications. The findings reveal that Al-Farabi's philosophy, which emphasizes the integration of knowledge, morality, and practical skills, is highly relevant in addressing the challenges of Society 5.0. This approach supports the development of a PAI curriculum that is adaptive to technological advancements while fostering a generation that is intellectually capable, morally grounded, and practically skilled to navigate the complexities of the digital era